Covid-19 and the Role of Halal Food - Rusydiana, Aam Slamet; Assalafiyah, Aisyah (European Journal of Islamic Finance, 2020)
This study aims to determine the map of the development of research on the halal food industry’s theme in the COVID-19 pandemic published by indexed journals. The study was conducted in August 2020. The analysis focused on the trends of the topics, keywords, authors and journals. The data analyzed were more than 50 digital object identifier equipped papers. The object of the study is a published journal published from 2019 to 2020. The data is then processed and analyzed using the VOSviewer application program to determine the bibliometric mapping of the development of COVID-19 research and the role of halal food. The results showed that the number of articles discussing the theme of halal food has been quite large in the last two years. Bibliometric visualization shows that the map of the development of COVID-19 research is divided into 4 clusters. Cluster 1 consists of 12 topics, cluster 2 consists of 12 topics, cluster 3 consists of 8 topics, and cluster 4 consists of 8 topics. This study’s findings are that there is special attention to the halal industry’s development, mostly halal food, to mitigate the prolonged health crisis’s impact.This study provides an overview of trends in the most popular topics, keywords, journals and authors in articles on halal food, thus providing information for researchers focused on research in the field of halal food. In the end, this theme has the potential to continue to be developed.